Correlation between mini-mental state examination and platelet ADAM10 expression in Alzheimer's disease - Manzine, Patrícia Regina; Barham, Elisabeth Joan; Vale, Francisco de Assis Carvalho do; Selistre-de-Araújo, Heloisa Sobreiro; Iost Pavarini, Sofia Cristina; Cominetti, Márcia Regina (Journal of Alzheimer's disease, 2013)
Previous studies have demonstrated a decrease in platelet ADAM10 expression among patients with Alzheimer's disease (AD) and healthy matched subjects. The association between cognitive tests and molecular biomarkers, such as platelet ADAM10, may contribute to an accurate AD diagnosis. The aim of this research was to investigate whether cognitive deficits in AD, assessed by Mini-Mental State Exam (MMSE), correlate with ADAM10 platelet levels and if that contributes to a more effective AD diagnosis. Elderly patients with probable AD (n = 30) and a non-AD control group (n = 25), matched by age, gender, and education level were evaluated. Platelet proteins were analyzed on SDS-PAGE (10%) and ADAM10 expression was identified by western blotting. β-actin was used as the endogenous control. The Spearman correlation coefficient between ADAM10 and MMSE ratio was obtained for each group. The MMSE ratio of AD subjects (0.45 ± 0.32) was significantly different (p < 0.001) compared to the non-AD group (1.14 ± 0.07). The relationship between MMSE ratio and ADAM10 expression was significant (r = 0.62, p = 0.0003) for the AD group. The combination of ADAM10 and MMSE at a cutoff ≤ 0.87 presented a sensitivity of 85%, and a specificity of 97% (AUC 0.99, 95% CI 0.92 -1.00), which was significantly better for AD diagnosis than the AUCs of MMSE (p = 0.05) and ADAM10 expression (p = 0.18) separately. The association of MMSE and ADAM10 expression was significantly better compared with MMSE and ADAM10 expression separately, thus providing and additional diagnostic tool for AD.